The Relationship Between Family Characteristics and Feeding Patterns with Stunting Incidence in Toddlers - Ritanti ritanti; Desty Wijayanti (Madago Nursing Journal, 2026)
Background: Stunting is a chronic growth disorder in children caused by long-term malnutrition. This condition remains a public health problem in Indonesia. Family characteristics and feeding practices play an important role in determining children's nutritional status. However, community-based empirical evidence is still limited. Therefore, this study aims to analyze the relationship between family characteristics, feeding practices, and stunting among children aged 12–59 months. Methods: This study used a cross-sectional design conducted in Limo Village, Depok City. The sample consisted of 328 mother-child pairs selected using probability sampling with cluster sampling technique, where all integrated health service posts (posyandu) were used as strata. Data were collected through a structured questionnaire to assess family characteristics and feeding patterns, as well as anthropometric measurements to determine stunting status. Data analysis was performed using the Chi-Square test with a significance level of 0.05. This study obtained ethical approval from the relevant ethics committee, and all respondents gave their consent after receiving an explanation. Results: The results indicate a significant association between family characteristics including maternal age, maternal education, family income, number of children, and family type and stunting (p < 0.05). Similarly, feeding practices were also significantly associated with stunting (p = 0.026). Furthermore, stunting was more prevalent among children of mothers with low educational attainment, families with incomes below the minimum wage, and those with suboptimal feeding practices. Conclusion: The incidence of stunting in toddlers is significantly influenced by family characteristics and feeding practices. These findings emphasize the importance of family-based interventions that focus on strengthening responsive parenting and proper feeding practices. Further research using a longitudinal design or intervention is recommended to support stunting prevention efforts at the community level.